PENGARUH BRAND ATRIBUTE DAN KUALITAS LAYANAN TERHADAP KEPUASAN DAN LOYALITAS WISATAWAN BERKUNJUNG KE DAYA TARIK WISATA TANAH LOT, TABANAN - Induyoga Aditama I Wayan; Surya Ida Bagus Ketut; Widiastuti Widiastuti (Jurnal Belantara, 2023)
Tanah Lot Tourist is one of the Tourist Destinations based on natural beauty and culture. Changes in tourist behavior in traveling, it is important to do research on the analysis of visitor behavior. The aims of this study include (1) to analyze the influence of Brand Attributes on tourist satisfaction; (2) to analyze the influence of Brand Attributes on tourist loyalty; (3) to analyze the influence of Brand Attributes on tourist loyalty mediated by tourist satisfaction; (4) to analyze the effect of service quality on tourist satisfaction; (5) to analyze the quality of tourists to tourist loyalty; (6) to analyze service quality on tourist loyalty mediated by tourist satisfaction; and (7) to analyze tourist satisfaction on tourist loyalty. This research method uses a quantitative approach with a sample of 100 respondents. The sampling technique in this study used accidental sampling and data collection through distributing questionnaires, interviews, observations, and literature studies.data analysis technique used Structural Equation Modeling (SEM) with the SmartPLS 3.3.3 Student Version analysis tool. The results of research on visitor behavior at Tanah Lot Tourist Attraction show that (1) Brand Attributes have a significant effect on tourist satisfaction; (2) Brand Attribute has no significant effect on tourist loyalty; (3) Brand Attribute has no significant effect on tourist loyalty which is mediated by tourist satisfaction; (4) service quality has a significant effect on tourist satisfaction; (5) tourist quality has a significant effect on tourist loyalty; (6) service quality has a significant effect on tourist loyalty which is mediated by tourist satisfaction; and (7) tourist satisfaction has a significant effect on tourist loyalty.